The Influence of Life Style, Product Diversity and Sales Promotions on Purchasing Decisions among Shopee Online Store Customers in Ambon City - Merry M. Pelupessy; Erlinda Tehuayo; Putri A. Jihan Dini (ProBisnis : Jurnal Manajemen, 2023)
The research uses associative research, namely a type of research that aims to analyze the relationship between one variable and other variables. The population in this research is consumers who have made purchases at the Shopee online store. The sample in this research was 100 respondents. The sampling method uses purposive sampling, which is adjusted to the research objectives or problems with the criteria of consumers who are active and have made purchases using the Shopee application. The data collection tool uses a questionnaire which has been tested for validity and reliability and then tests the quality of the data by assessing the outer model or measurement model and the inner model or structural model which is calculated using PLS, and the analysis method in this research uses the Partial Lest Square (PLS) analysis method. The results of this research show that Lifestylepositive influence onbuying decisiononShopee online shop in Ambon City, Product Diversity noinfluence onbuying decisiononShopee online store in Ambon City, and Sales Promotionspositive influence onbuying decision onShopee online shop in Ambon City.